Assessment of Orofacial Dysfunctions Using the 'Nordic Orofacial Test-Screening' Method Among Children with Cerebral Palsy and its Correlation with Dental Caries - A Cross-Sectional Study - Mihir Nayak; Sarakanuru. K. Srinath; Tejavathi Nagaraj; Umme Azher; Shinie R. Goveas; Shereen Idiculla (Wolters Kluwer Medknow Publications, 2024)
Background: Nordic Orofacial Test-Screening (NOT-S) is an all-inclusive method of screening for oro-facial dysfunctions (OFDs). Objectives: To evaluate the OFD of children affected with cerebral palsy (CP) employing NOT-S and to detect the correlation of OFD with dental caries. Methods: Seventy-six children aged 4 to 14 years affected with CP had been included in the cross-sectional study. A single trained examiner who was experienced in using the NOT-S method performed screening and interpreted the results. Dental caries was determined based on the criteria advocated by the World Health Organization, 1997. Results: The most consistently detected OFD during interview were observed in the categories of habits, chewing/swallowing and drooling. Oral motor dysfunctions and speech issues were predominantly seen when examined. A very weak positive correlation was noticed amid NOT-S scores and caries in primary dentition, whereas almost no correlation with caries in permanent dentition was noticed. Conclusion: The NOT-S protocol was a successfully valuable tool for holistic assessment of OFD in children affected with CP.